2014
DOI: 10.1002/cmdc.201402409
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tacrine‐Grafted Ugi Adducts as Multipotent Anti‐Alzheimer Drugs: A Synthetic Renewal in Tacrine–Ferulic Acid Hybrids

Abstract: Herein we describe the design, multicomponent synthesis, and biological, molecular modeling and ADMET studies, as well as in vitro PAMPA-blood-brain barrier (BBB) analysis of new tacrine-ferulic acid hybrids (TFAHs). We identified (E)-3-(hydroxy-3-methoxyphenyl)-N-{8[(7-methoxy-1,2,3,4-tetrahydroacridin-9-yl)amino]octyl}-N-[2-(naphthalen-2-ylamino)2-oxoethyl]acrylamide (TFAH 10 n) as a particularly interesting multipotent compound that shows moderate and completely selective inhibition of human butyrylcholines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 71 publications
1
50
0
3
Order By: Relevance
“…Contilisant showed improved irreversible inhibition of MAOB compared to ASS234, which prefers MAOA.T he affinities for binding at human H3R as the target and H4R, the structurally most homologous G-protein-coupled receptor, as an off-target were measured ( Table 1). Ab [25][26][27][28][29][30][31][32][33][34][35] ), comparable to that offered by melatonin ( Figure 2). Surprisingly,A SS234 showed remarkable affinity at H3R, but the highest affinity was found for 2 and contilisant, which both contain the propyloxy linker connected to pyrrolidine and piperidine moieties,r espectively.G ood affinities were also found for 6,c ontaining ar elated H3R pharmacophore,and 7,which lacks the propargylamine group but features the propyloxy linker.C ompounds with ethyloxy or pentyloxy spacers showed moderate H3R affinities.T hese findings confirmed previously obtained SAR results for H3R antagonists.…”
mentioning
confidence: 77%
“…Contilisant showed improved irreversible inhibition of MAOB compared to ASS234, which prefers MAOA.T he affinities for binding at human H3R as the target and H4R, the structurally most homologous G-protein-coupled receptor, as an off-target were measured ( Table 1). Ab [25][26][27][28][29][30][31][32][33][34][35] ), comparable to that offered by melatonin ( Figure 2). Surprisingly,A SS234 showed remarkable affinity at H3R, but the highest affinity was found for 2 and contilisant, which both contain the propyloxy linker connected to pyrrolidine and piperidine moieties,r espectively.G ood affinities were also found for 6,c ontaining ar elated H3R pharmacophore,and 7,which lacks the propargylamine group but features the propyloxy linker.C ompounds with ethyloxy or pentyloxy spacers showed moderate H3R affinities.T hese findings confirmed previously obtained SAR results for H3R antagonists.…”
mentioning
confidence: 77%
“…As presented in Tables 3 and 4, the ORAC values for compounds in the different chemical series ranged from 4.98 to 9.10 in series I , from 2.14 to 7.89 in series II , and from 2.96 to 9.42 in series III . Accordingly, compared to ferulic acid, the antioxidant reference standard with an ORAC value of 3.74 Trolox equivalents (TE), all compounds showed a strong capacity to scavenge a peroxyl radical.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Within this series, incorporation of either electron‐donating or electron‐withdrawing substituents at position C4’ resulted in compounds with significantly less antioxidant power ( 2 , 3 , 4–8 ). In fact, 1‐(2,5‐dimethoxybenzyl)‐4‐arylpiperazines ( 1 ), with an impressive TE value of 9.10, is the second most potent antioxidant agent found among all compounds tested, 2.4 times more potent than ferulic acid . In this respect, comparing the TE values for compounds 4–8 , it is observed that the stronger the electron‐withdrawing capacity of the substituent, the lower the antioxidant power of the compound.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Erwähnenswert bezüglich der molekularen Eigenschaften von Contilisant, erhoben mit molsoft, [26] ist die hçhere Hydrophilie (MolLogP = 3.7) im Vergleich zu ASS234 (MolLogP = 5.5), was einen verbesserten Wirkstoff-¾hnlichkeitsfaktor bestätigt. [28] Die neuroprotektiven Fähigkeiten wurden anhand dreier unterschiedlicher Toxizitätsmechanismen untersucht, die bei Morbus Alzheimer an neurodegenerativen Prozessen beteiligt sind: [29] nicht aktiv [25] nicht aktiv [25] Deprenyl nicht aktiv [25] nicht aktiv [25] Donepezil [4] Eine potenzielle Verbesserung der Erinnerungs-und Lernfähigkeit in vivo durch ASS234 und Contilisant wurde mittels "Novel-Object-Recognition"(NOR)-Test in Mäusen (Abbildung 3) untersucht, [30] vor und nach Gabe von Lipopolysaccharid (LPS), das eine signifikante Reduktion der NOR-Leistung verursacht. Die Ergebnisse zeigen die Fähigkeit von Contilisant und ASS234, die Blut-Hirn-Schranke mittels passiver Diffusion zu überwinden.…”
unclassified
“…Die antioxidative Kapazitätd er Hybride 1-5 und 7 wurde mittels "Oxygen-Radical-Absorbance-Capacity"(ORAC-FL)-Test gemessen (Tabelle 1), [27] wobei alle MTLs gute Radikalfänger-Eigenschaften zeigten und Contilisant ähnliche Werte erzielte wie die Positivkontrolle Ferulasäure (3.74 AE 0.22 TE). [28] Die neuroprotektiven Fähigkeiten wurden anhand dreier unterschiedlicher Toxizitätsmechanismen untersucht, die bei Morbus Alzheimer an neurodegenerativen Prozessen beteiligt sind: [29] nicht aktiv [25] nicht aktiv [25] Deprenyl 0 30…”
unclassified